ANALISIS TINGKAT RISIKO PEMBIAYAAN MUSYARAKAH TERHADAP RETURN ON ASSETS - Mustofa Mustofa; M. Manshur Idris (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2019)
Sharia banks are present because of people's needs for alternative transactions that are without interest or usury. One form of transactions in Islamic banks is financing including mudharabah, musyarakah and murabahah which are the most frequently used contracts. Musharaka financing is the biggest contributor to assets in Islamic banks. So the high financing will affect the level of profitability of Islamic banks. The researcher wanted to examine the risks of musharaka financing to the profitability of BPR Syari'ah Situbondo which will be projected with ROA. With the formulation of problem 1) What was the procedure for financing Musyarakah in the Syari'ah Situbondo Rural Credit Bank? 2) What did risks occur in musyarakah financing to return on assets? The approach used in this research was qualitative research. While the type of research used by researchers in this research was descriptive research means describing the variables, one by one. The results showed that the Musharaka financing procedure at the Syari'ah Situbondo People's Financing Bank by fulfilling the requirements to become a BPR Syari'ah Situbondo customer by signing and filling out an account bookkeeping application form containing a complete identity and must follow the procedures determined by the BPR Syari'ah Situbondo. Risks that occur were usually when the customer did not only have one project. The funds that had been disbursed by the SRB will be used for other projects. So that the risk of musyarakah financing affects the profitability of banks.